(untitled) (Yearbook - Faculty of Economics, 2018)
The capital investment from abroad means establishing an operations at local level in aim production and distribution of goods and services. Foreign direct investment in Central and Eastern Europe has ﬁ nanced massive new manufacturing capacities, especially in automobile, electronics, furniture, pharmaceutical sectors, but also retail sector, banking and ﬁ nance, telecommunication and transport sector. FDI in CEE has played a key role in boosting economic growth and shaping legislation since 1990. The structure of the paper will be as follows: The ﬁ rst part describes the foreign direct investment in Central and Eastern Europe and the ﬂ ow of FDI to different countries in CEE. The second part of the paper is about factors to FDI and some measures and policy practices for attracting FDI in CEE. The third part of the paper analyses the inﬂ uence of FDI for CEE countries, and positive and negative effects from FDI. And The fourth part of the paper gives overview of the FDI structure by sectors and country of origins and weather the investments were an result of the privatization process or green ﬁ eld investments.